2014
DOI: 10.2166/wp.2014.207
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water safety plans: barriers and bridges for small systems in Alberta, Canada

Abstract: Water safety plans provide a relatively new management approach for identifying and addressing risks in a water supply. In 2011, the province of Alberta (Canada) became the first jurisdiction in North America to require that all water supplies develop drinking water safety plans (DWSPs). This research explored the implementation of DWSPs through the experiences of 'early adopter' operators who work in small communities. Specifically, inperson open-ended qualitative interviews with operators from 15 small commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 22 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…Although, the basic principles for developing and implementing a WSP are the same in all countries, there is no rigorous methodology that dictates a specific way of developing it. Therefore, WSPs can be applied to a wide range of water utilities regardless of their location, degree of complexity and production capacity [34]. The first countries involved in the implementation of WSPs were Iceland in 1997 [13] and Australia in 1999 [12].…”
Section: Wsps Implementation In European Countriesmentioning
confidence: 99%
“…Although, the basic principles for developing and implementing a WSP are the same in all countries, there is no rigorous methodology that dictates a specific way of developing it. Therefore, WSPs can be applied to a wide range of water utilities regardless of their location, degree of complexity and production capacity [34]. The first countries involved in the implementation of WSPs were Iceland in 1997 [13] and Australia in 1999 [12].…”
Section: Wsps Implementation In European Countriesmentioning
confidence: 99%
“…External support is needed The dilemma analysis found that lack of empowerment creates barriers to improving water safety through monitoring. This is also reflected in the literature on water safety planning, which frequently highlights inadequate financing [34][35][36][37] and capacity 34,35,[38][39][40] as substantial barriers to successful implementation. In rural areas in particular, inadequate financing and capacity have meant that water safety planning efforts focus on the early stages of the approach (assembling a team, describing the water supply and identifying hazards, developing and implementing a plan for improvement) but neglect the latter stages of monitoring, verification, and iterative learning 33,39 , which are crucial to the effectiveness and sustainability of the approach 29,37 .…”
Section: Contextualising Monitoring Resultsmentioning
confidence: 98%
“…The dichotomy sustains the view that taking responsibility for water safety is an excessive burden. As reflected in the literature, this view of monitoring-and water safety planning more broadly-as burdensome is a key difficulty for securing buy-in to the approach 35,43,44 . Though we have focussed in this study on rural context, the quantity versus quality dichotomy has broader relevance.…”
Section: Early Adoption Of Water Safety Planningmentioning
confidence: 99%
“…Ferguson et al, 2013), water safety planning (e.g. Perrier et al, 2014) and risk governance (e.g. Dunn et al, 2015;Mauelshagen et al, 2014).…”
Section: Methodsmentioning
confidence: 99%